Impact of the Scatterer Type on Ultrasound Wave Propagation in Microstructure Composites: Calculation and Application - Yang, Yuming; Duan, Huilong; Zheng, Yinfei (Frontiers in Materials, 2022)
This study is motivated to quantitatively analyze the differences among various multiple scattering models to determine the role played by the scatterer type in ultrasonic wave propagation. By calculating the transmission and reflection coefficients of the composites, the results of multiple scattering theoretical models of different scatterer types have been evaluated. The problem of acoustic properties in a fluid matrix containing different types of micron-scale scatterers operating in the ultrasound frequency range is considered. Theoretical calculations are conducted for composites with different mechanical properties. Meanwhile, the theoretical results have been compared with numerical finite element method simulations, which can be regarded as a benchmark to verify the validity of different theoretical models. The results show that the composites can achieve negative acoustic properties by selecting appropriate resonant scatterers, paving the way for searching ultrasonic metamaterials with desired negative acoustic properties. We further explored the application of microstructure ultrasonic metamaterials by enhancing the ultrasound transmitted energy through the high-impendence skull layer, having the potential for non-invasive ultrasound brain imaging and therapy.